Ships and air guns reduce social interactions in humpback whales at greater ranges than other behavioral impacts - Dunlop, R.A.; McCauley, Robert; Noad, M.J. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
© 2020 Elsevier Ltd